An Improved Method For Assessing The Impact Of Management Journals - Rosenstreich, Daniela; Wooliscroft, Ben (Asian Academy of Management (AAM), 2013)
Despite their limitations, journal rankings and impact data often form the basis of evaluations of research performance. Recent advances in citation analysis may facilitate the creation of journal rankings with broader coverage, particularly in terms of international coverage. This study explores three sources of citation data: Web of Science, Scopus and Google Scholar. It was found that Web of Science indexes approximately one-fifth of all academic management titles and includes fewer citations than Google Scholar. Six rankings of management journals were combined to produce a list of 57 titles. Overall, the analysis of citation data in this study suggests that the gindex provides an improved mechanism for measuring the impact of journals.